A STUDY ON CERTAIN BLOOD BIOMARKERS OF PREGNANT CHOLISTANI COWS - Z. Batool; M. Lashary; U. Farooq; M. Idris; U. Riaz; M. Ali; M. R. Yousaf; A. Khurshid (Journal of Animal and Plant Sciences, 2018)
The study investigates the alterations in hematological and cortisol levels in three trimesters of pregnancy in the cows of Cholistani breed being reared under nomadic pastoralism production system at Cholistan desert, Pakistan. Pregnant cows (n=12) ranging between 3 to 5 years of age were incorporated in the study and were grouped as ( n= 04 each) viz. st nd rd belonging to 1 , 2 and 3 trimesters of pregnancy. Blood was collected and analyzed for salient hematological parameters through manual methods, and for cortisol assessment through commercial ELISA kit. Each cow was bled thrice in a month hence making a total of 36 blood samples. The mean values for Total Erythrocytic Count and hemoglobin were higher (P<0.05) in the first as compared to the second and third trimesters, respectively. There was no difference ( P> 0.05) in the Packed Cell Volume during the three trimesters of pregnancy. Regarding the erythrocytic indices, an increase (P<0.05) was observed for Mean Corpuscular Volume in the three trimesters of pregnancy. Whereas, a decrease (P <0.05) was noted for Mean Corpuscular Hemoglobin Concentration. There was no difference (P>0.05) for Mean Corpuscular Hemoglobin across the length of pregnancy. There was an increase (P<0.05) in the Total Leukocytic Count in the second and third trimesters of pregnancy, however,there was no difference (P>0.05) in the Differential Leukocytic Count during the three trimester of pregnancy. Cortisol tended to increase (P<0.05) with advancing stage of pregnancy. The alterations in hematological parameters and cortisol level of pregnant Cholistani cows are marked in each trimester. Hemodilution, an enhanced TLC and cortisol level are the main features of pregnancy in pregnant Cholistani cows. However, in general, they tend to maintain a harmonious pattern which may be an indication of their innate adaptive stress-tolerant ability. documented (Sattar and Mirza, 2009; Mir et al., 2008;
Keywords: Cortisol; Cholistani cows; hematology; stress indicators.